Continuous glucose monitoring system versus self-monitoring blood glucose in type 1 diabetes mellitus children (RoSEC): a randomized controlled trial - Bachok, Norsaadah; Hussain, Suhaimi; Muhd Helmi, Muhd Alwi (Malaysian Paediatrics Association, 2021)
Objectives: The primary and secondary objectives were to compare the glycaemic control and frequency of hypoglycaemia between continuous glucose monitoring system (CGMS) and self-monitoring blood glucose (SMBG). Methods: A single centre, randomised, parallel-group controlled trial was conducted involving twenty-two type one Diabetes Mellitus (T1DM) patients with the mean age of 13.8 years assigned to either intervention or control group. All respondents wore the CGMS device at the beginning of the study. Intervention group (n=11) had their insulin adjusted based on the CGMS data, while the control group (n=11) was based on SMBG. Monthly average blood sugar level (BSL) and monthly mean hypoglycemic events per week (HE/wk) were measured at baseline, first month, second month, and third month. HbA1c levels were measured at baseline and in the third month. Results: The baseline characteristics were similar. The data were analysed using repeated measure analysis of variance (ANOVA). The mean difference of HbA1c within the group was not statistically significant with p=0.322. There were significant differences in the monthly mean HE/wk within and between groups, p=0.004, and p=0.037. Conclusion: In conclusion, CGMS is equivalent to SMBG in optimising glycaemic control but is more effective in detecting hypoglycaemia in children.